The economic and social impact of European funds in the Romanian agriculture - Valentin Marian Antohi; Liliana Mihaela Moga (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
This paper aims to identify and analyze the stages undergone by the Romanian agriculture, within the context of integration in the European Union, and the transformation that occurred in the aftermath of accession. On this line, the social and economic effects of agriculture integration and the direction of the Romanian agriculture development have been forecasted through a research conducted at the rural area level of the North East Development Region. The research was based on data collected from the village book that includes reference to the village social and economic environment, on information gathered from the statistical surveys and county institutions, which were supplemented by the answers to a questionnaire designed for achieving social and economic surveys on drafting the rural development in the investigated area. The results allowed the synthesis of the main effects of integration in the European Union on agriculture, with reference to the research area. The profile of local rural development in the next period was shaped after forecasting the effects of initiatives for development projects to attract European funds.
Keywords: 330; European funds; agriculture; economic effects; social effects; rural development